THYROTOXICOSIS WITH HIGH TRIIODOTHYRONINE (T3) AND LOW THYROXINE (T4): A CASE SERIES AND REVIEW OF CLINICAL AND MANAGEMENT - Jangjit, Sajja; Sarinnapakorn, Veerasak (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The thyroid function test with high FT3 and low FT4 is uncommon in hyperthyroidism patients. There is no clear treatment guideline, causing difficulty in adjusting the medication. The mechanism of this group of thyrotoxicosis is the increased conversion of T4 to T3 in the peripheral tissue. There has been an increase in dehydrogenase types 1 and 2 in a few reports. Furthermore, no relationship with thyroid cancer has been studied. This study aims to review clinical management and outcomes in thyrotoxicosis patients with high FT3, low FT4, and TSH. METHODOLOGY The data, including gender, age, TSH, FT3, FT4, medication, surgery, and tumor pathology, were collected retrospectively between 2015-2022 from Rajavithi Hospital's database. The inclusion criteria for selecting patients were: (1) 18 years old or over; and (2) at least one laboratory result shows low TSH with high FT3 and low FT4 levels. RESULTS Between 2015-2022, we found 13 cases of thyrotoxicosis with at least 1 laboratory result showing low TSH, high FT3, and low FT4. Despite antithyroid drug alone or a block and replacement regimen, we were unable to maintain both FT3 and FT4 in the normal range. Eight patients were treated with a "block and replace regimen," 3 patients were treated with antithyroid drug alone, 2 patients had not taken any medication due to early surgery, and another refused treatment. Eleven patients underwent thyroidectomy, 5 patients had follicular thyroid carcinoma, 1 case had papillary thyroid cancer and 5 patients had benign hyperfunctioning adenoma. CONCLUSION This result suggests that the patients with high FT3 and low FT4 were unlikely to maintain FT3 and FT4 in the normal range with either an antithyroid drug alone or block and replace regimen. The mechanism of T3 thyrotoxicosis patients is caused by the increased conversion of thyroxine (T4) to triiodothyronine (T3). Moreover, we found a high malignancy rate in this type of patient.